SISTEM INFORMASI AKUNTANSI SEBAGAI DETERMINAN KINERJA KEUANGAN PADA PERUSAHAAN JASA KONSTRUKSI DI KOTA MATARAM - I Gede Pasek Suryadnyana Putra; Lukman Effendy; Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2022)
This study aims to examine the influence of accounting information system on financial performance on a construction services company in the city of Mataram. This research uses primary data and secondary data, primary data obtained from questionnaires to the respondents, which is the employees who work directly with the accounting information system construction services company in the city of Mataram, while the secondary data obtained from the financial data of the company for 3 years. The sampling technique used is purposive sampling with the sampling results a total of 47 companies. Data were processed using the software smartPLS the latest version 3.3.3. The results of this study indicate that accounting information systems affect the company's financial performance. The success of an accounting information system will provide impact and benefits on the performance of individuals and companies, so that will increase the effectiveness and efficiency of the company. the implications of this study can be used as input by the business of construction services, where the company should also pay attention to the use of accounting information systems that are appropriate and adequate for the company to improve the performance of the company.